DEFICIT FINANCING DI INDONESIA: SATU KAJIAN EMPIRIK - Sriyana, Jaka (Jurnal Ekonomi & Studi Pembangunan, 2006)
The fiscal policy has become an important issue in Asian countries, including Indonesia. In recent years, a number of papers have focused on the examination official performance, including fiscal sustainability and the relationship between fiscal and monetary variables. This paper attempts to analyze the relationship between fiscal variables, including government expenditure, tax and price in Indonesia. This paper applied cointegration and Vector Error Correction Model (VECM) to analyze the relationship between government expenditure and tax. The result shows that, there is strongly long run relationship between fiscal and monetary variables. A more active fiscal policy and a better fiscal management must be practiced in Indonesia.